2004
DOI: 10.1007/s10350-004-0625-9
|View full text |Cite
|
Sign up to set email alerts
|

Small-Bowel Infarction From Disseminated Aspergillosis

Abstract: This diagnosis should be considered when neutropenic patients show abdominal pain and distention with fever. Repetition of Aspergillus antigenemia, search for others aspergillosis localizations, CT scan, and colonoscopy with biopsies should be performed until diagnosis allows the administration of early antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…It is rapidly progressive with reported mortality rates of 80–90% 2 3. A detailed medical, drug and travel history is therefore paramount in cases of critically unwell patients in whom the pathogenesis is unusually aggressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is rapidly progressive with reported mortality rates of 80–90% 2 3. A detailed medical, drug and travel history is therefore paramount in cases of critically unwell patients in whom the pathogenesis is unusually aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…Of those with invasive disease, 41–47% will have involvement of the gastrointestinal tract 2. These patients may develop bowel obstruction and other complications including intestinal ischaemia, bleeding, necrosis and perforation 3. However, diagnosis of gastrointestinal aspergillosis is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…5 The main localizations of aspergillosis are the lung and cranial sinuses, with secondary dissemination to the brain, gastrointestinal tract, liver, and heart. 5 According to one report, the gastrointestinal tract was the site of 41% of deep fungal infections in immunocompromised patients, with 22% affecting the lower part of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoalveolar lavage fl uid should also be tested for aspergillosis because gastrointestinal invasive aspergillosis is usually part of a disseminated disease with lung involvement. 5,7 However, the fi nal diagnosis is most often established by the pathologic fi ndings of a surgically resected specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Schwesinger et al reported that 25 of 27 patients with aspergillosis had pulmonary involvement [6]. Disseminated aspergillosis can cause bowel infarction or diffuse peritonitis due to small bowel perforation [7][8][9][10]. Moreover, the majority of these patients succumbed within a short time [11].…”
Section: Introductionmentioning
confidence: 98%